The Soviet magazine "Rabotnitsa" in 1920-1930: design and the specific practice of visual genres - МинаеваОльга Дмитриевна (Communications. Media. Design, 2017)
The article analyses the making of the Soviet magazine "Rabotnitsa" (in English translation “The Working Woman”) in 1920-1930 from the perspectives of design and specific practices of visual genres, such as illustrations, photoworks and poster art. During this period, special attention was paid to the visual genre, which is associated with a low level of literacy of the female audience in Soviet Russia. All design elements of the magazine carried a meaning and enhanced the effectiveness of the promotion of the equality of Soviet women. The author points that the magazine was positioned as “richly illustrated” with 30 or 40 illustrations for 34 pages of every magazine in the 1920s. The core audience of the magazine was defined by the editorial as “every female worker of the factory or plant, wife of the worker, his mother, his sister”. The editorial claimed the main goal of the magazine as “the liberation of every woman from the housewife responsibility oppression”, so every woman “can become a builder of society of communism”. The author points that the magazine covers primarily focused on women of different professions, which were earlier claimed as “man-only”. Feminine topics, such as fashion or cookery, were covered scantily. The editorial policy was to tell about main political topics or questions “of current interest” through illustrations, pictures and photographs.